Effect Teams Game Tournament Model Assisted by Plickers Applications Media on The Understanding Mathematics Concepts - Stiadi, Elwan (International Journal of Innovation and Education Research, 2024)
This study aims to analyze the effect of the Teams Games Tournament (TGT) model assisted by Plickers application media on the understanding of mathematical concepts of class XI students of SMA Negeri 10 Bengkulu City.This type of research is a quasi experimental research with a non-equivalent pretest-posttest control group design. The population in this study were all eleventh grade students of SMA Negeri 10 Bengkulu City in the 2023/2024 academic year. The sample of this study was taken using purposive sampling technique in which XI MIPA 3 class totaling 20 students as an experimental class taught using the Teams Games Tournament (TGT) model assisted by Plickers and XI MIPA 2 class totaling 32 students as a control class taught with a direct learning model. Data collection was carried out with a mathematical concept ability test instrument. The hypothesis test results show that the value sig. (2-tailed) is 0.000 < = 0.05 and supported by 0.581 with moderate category. Therefore, it can be concluded that there is a significant effect of the Teams Games Tournament model assisted by Plickers application media on the ability to understand mathematical concepts of class XI students of SMA Negeri 10 Bengkulu City.